The Association Between Green Tea Consumption with Cardiovascular Related Mortality: A Meta-Analysis - Isnani Nurhayati; Anas Rahmad Hidayat; Tri Yuniarti; Harpeni Siswati Budi (Masters Program in Public Health, 2021)
Background: Tea (green or black) are among the most widely consumed beverages in adults worldwide. Recently, numerous studies claimed that green tea intake have been associated with reduced mortality, including cardiovascular disease related mortality. This study was aimed to investigate the association between green tea consumption with cardiovascular related mortality.Subjects and Method: This was a systematic review and meta-analysis study used articles which published in 2000 to 2021 from online databases, such as PubMed, ResearchGate, Science Direct, Google Scholar, and EBSCO. The dependent variable was cardiovascular related mortality. The independent variables was green tea consumption. The data was analyzed by RevMan 5.3 software. This study used the eligibility criteria with the PICO model, populations: COVID-19 general adults, intervention: >1 cups green tea consumption. comparison: null or <1 cup green tea consumption, outcome: cardiovascular related mortality. The inclusion criteria were an article describing the effect or relationship of green tea consumption with cardiovascular related mortality, original research, and study of cohort contain effect size of hazard ratio and match with the intervention design. The keywords used to search the database were